Implementasi Falsafah Kato Nan Ampek Dalam Pembelajaran PAI Di SMA Muhammadiyah Padang Panjang - reny rahmelia (Universitas Islam Sultan Agung, 2026)
Kato nan ampek is a linguistic politeness norm in Minangkabau culture that encompasses four principles: kato mandaki (respect towards elders), kato manurun (towards younger individuals), kato malereng (towards those honored), and kato mandata (towards peers). This study examines the implementation of kato nan ampek values in Islamic Religious Education teaching, as well as supporting and inhibiting factors. This is a field research study conducted through interviews with Islamic Religious Education teachers, curriculum deputies, and students from grades XI and XII, along with observations. The results indicate effective integration of kato nan ampek values such as raso (mutual respect), pareso (empathy), sopan (politeness), and kasih sayang (compassion) in Islamic Religious Education activities like debates and group discussions, which promote harmonious interactions. Supporting factors include local curriculum, active teacher roles, school programs, and a supportive environment, while inhibiting factors stem from diverse student backgrounds and technological influences. The conclusion states that this implementation strengthens student character, preserves Minangkabau culture, and promotes ethical communication, with recommendations for expanding application and teacher training.